2019
DOI: 10.1021/acsearthspacechem.9b00312
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Reactions in Highly Functionalized Organic Aerosols during Thermal Desorption

Abstract: Atmospheric organic aerosols (OA) are complex mixtures of organic molecules that are usually highly functionalized through various oxidative processes. Understanding the volatilities and chemical compositions of OA is key to elucidating their environmental impacts. Thermal desorption coupling to mass spectrometry has been used as the main approach to examine both aspects of OA. In this work, we investigated the thermal desorption-induced chemical compositional change of OA from heterogeneous oxidation of gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 70 publications
1
50
1
Order By: Relevance
“…Thus, different drift times usually suggest different structures. In our previous studies, we have demonstrated that the IMS-TOF is able to clearly separate structural isomers. ,,, Using the ESI in both the positive (+) and negative (−) ion modes allows for detections of the majority of the SOA constituents. An overview of the SOA molecular compositions is shown in Figures S10, S11 …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, different drift times usually suggest different structures. In our previous studies, we have demonstrated that the IMS-TOF is able to clearly separate structural isomers. ,,, Using the ESI in both the positive (+) and negative (−) ion modes allows for detections of the majority of the SOA constituents. An overview of the SOA molecular compositions is shown in Figures S10, S11 …”
Section: Results and Discussionmentioning
confidence: 99%
“…The SOA samples were then characterized offline by the IMS-TOF with electrospray ionization (ESI) (Tofwerk Inc. and Aerodyne Research Inc., t/Δt ∼ 100) through direct infusion or analyzed by the GC-EI-MS (Agilent Inc., 7890 GC and 5975 MSD) after derivatization (by additions of 25 μL N,O-Bis­(trimethylsilyl)­trifluoroacetamide (BSTFA) and 25 μL pyridine, both reagents from Sigma-Aldrich). Both analytical methods have been described in detail in our prior studies. , …”
Section: Materials and Methodsmentioning
confidence: 99%
“…The IMS separation could resolve isomeric products beyond the typical mass spectra shown in Figure . The major isomers for each chemical formula in individual OA heterogeneous oxidation experiments could be obtained and the CID fragmentation mass spectra for individual isomers could help differentiate and possibly elucidate the chemical structures between them. ,,, Two generations of functionalization products were observed in the studied systems. Figure presents the isomer-resolved drift time spectra (i.e., “driftgrams”) of these functionalization product formulas for all of the studied OA proxies.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it is well established that monofunctional ethers and esters are also stable and unreactive at temperatures above 400 C (Steacie 1933;Hurd and Blunck 1938). Conversely, organic peroxides decompose in the neighborhood of 100 C (Benson and Shaw 1970) and multifunctional compounds containing various combinations of hydroxyl, carboxyl, and carbonyl groups may be susceptible to thermal decomposition at temperatures <100 C (Zhao et al 2020). As such, when using the vaporizer it is recommended that particleand gas-phase composition be monitored to identify the occurrence of thermal decomposition.…”
Section: Gas-wall Partitioning Experimentsmentioning
confidence: 99%